Perfil epidemiológico e avaliação de fatores de risco para doença cardiovascular em pacientes atendidos em uma clínica escola de fisioterapia - Edilson Francisco Ferreira; Rita de Cássia de Assis; Ana Karla de Nogueira Faria; Camila Gomes Chaves; Alice Shaia Delmiro de Souza; Henrique Poletti Zani; Kelly Cristina Borges Tacon; Daniella Alves Vento (UniEVANGÉLICA, 2018)
Objective: To define the epidemiological profile and to evaluate the prevalence of risk factors for cardiovascular diseases in a Clinical School of Physiotherapy. Methods: This is a descriptive study, with patients attended at a Clinical School of Physiotherapy, aged over 18 years. A personal file and the International physical activity questionnaire and the collection of hemodynamic and respiratory variables were applied. Results: 60 patients were evaluated in the clinic, 75% were female and 75% were residents of the city of Anápolis-GO. The mean age was 57.75 ± 15.33 years, height 152.1 ± 41.28 cm and weight 71.68 ± 13.34 kg. The mean overall body mass index was 26.78 ± 3.964 kg / m², systolic blood pressure 121.8 ± 12.69 mmHg, diastolic 78 ± 8.79 mmHg, heart rate 76.82 ± 11.05 bpm, and respiratory rate 17 ± 3.73 ip. Of those evaluated, 8.3% were smokers, 11.6% were alcoholics and presented a diagnosis of cardiovascular diseases, some with more than one diagnosis, being 73.3% with systemic arterial hypertension, 48.3%, diabetes mellitus and 40% hypercholesterolemia . The family history found were hypertension 66.6%, diabetes mellitus 48.3%, hypercholesterolemia 40%, acute myocardial infarction 21.6% and stroke 20%. The majority of the sample was sedentary, accounting for 51.7% of the cases. Conclusion: Most of the participants were female, older than the fifth decade of life, living in the city of Anápolis / GO. There were low rates of smoking, alcoholism, high prevalence of sedentarism and obesity, which in this perspective suggests the application of health prevention measures to clarify the risk factors for cardiovascular diseases.